Is there a role for tau glutathione transferases in tetrapyrrole metabolism and retrograde signalling in plants?. (22nd June 2020) - Sylvestre-Gonon, Elodie; Schwartz, Mathieu; Girardet, Jean-Michel; Hecker, Arnaud; Rouhier, Nicolas
Abstract : In plants, tetrapyrrole biosynthesis occurs in chloroplasts, the reactions being catalysed by stromal and membrane-bound enzymes. The tetrapyrrole moiety is a backbone for chlorophylls and cofactors such as sirohaems, haems and phytochromobilins. Owing to this diversity, the potential cytotoxicity of some precursors and the associated synthesis costs, a tight control exists to adjust the demand and the fluxes for each molecule. After synthesis, haems and phytochromobilins are incorporated into proteins found in other subcellular compartments. However, there is only very limited information about the chaperones and membrane transporters involved in the trafficking of these molecules. After summarizing evidence indicating that glutathione transferases (GST) may be part of the transport and/or degradation processes of porphyrin derivatives, we provide experimental data indicating that tau glutathione transferases (GSTU) bind protoporphyrin IX and haem moieties and use structural modelling to identify possible residues responsible for their binding in the active site hydrophobic pocket. Finally, we discuss the possible roles associated with the binding, catalytic transformation (i.e. glutathione conjugation) and/or transport of tetrapyrroles by GSTUs, considering their subcellular localization and capacity to interact with ABC transporters. This article is part of the theme issue 'Retrograde signalling from endosymbiotic organelles'.